THE ASTROMETRIC RESULTS OF OBSERVATIONS OF PERIODICAL COMETS AT KT-50 TELESCOPE IN RI “MAO” - Pomazan, A. V.; Maigurova, N. V.; Shulga, O. V. (Одеські астрономічні публікації, 2017)
The astrometric results of the observations of 10 periodical comets in 2017 are presented. The observations were made with telescope KT-50 telescope in RI «Mykolaiv Astronomical Observatory». The differences between the measured from observations (O) and calculated from ephemeris (C) positions and their mean square errors (MSE) were calculated. The ephemeris positions were taken from online computation service HORIZONS (JPL NASA, USA). For the measured positions the average MSE values are 0.17˝ in right ascension and 0.18˝ in declination respectively. Analysis of the values (О-C) before and after additions of obtained positions to Minor Planet Center (MPC) database revealed a gradual decrease of these differences with respect to the ephemeris. This indicates that the using of the new high-precision positions allows us to refine the calculated ephemeris. As well improvement and lengthening of the astrometric datasets play important role in the modeling of the cometary nongravitational effects.